2016
DOI: 10.1007/s10517-016-3375-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Neural Stem Cells from Human Cortical Brain Structures In Vitro

Abstract: Comparative immunohistochemical analysis of the neocortex from human fetuses showed that neural stem and progenitor cells are present in the brain throughout the gestation period, at least from week 8 through 26. At the same time, neural stem cells from the first and second trimester fetuses differed by the distribution, morphology, growth, and quantity. Immunocytochemical analysis of neural stem cells derived from fetuses at different gestation terms and cultured under different conditions showed their differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Here, as well as in our earlier publication we showed that NSPCs maintained in FSC-containing medium supposed to promote astrocytic diffentiation, still capable of expressing such "stemness" markers as nestin and Lex/SSEA1, as well as an early marker of neuronal differentiation βIII-tubulin. Their expression is mostly localized in neurosphere-like floating cell aggregates [21] . Probably, maintaining of NSPCs cultures in serum-containing media results in the accumulation of the least differentiated cells in neurospheres, while more differentiated cells adhere to cultural plastic and are eliminated at passaging.…”
Section: Discussionmentioning
confidence: 99%
“…Here, as well as in our earlier publication we showed that NSPCs maintained in FSC-containing medium supposed to promote astrocytic diffentiation, still capable of expressing such "stemness" markers as nestin and Lex/SSEA1, as well as an early marker of neuronal differentiation βIII-tubulin. Their expression is mostly localized in neurosphere-like floating cell aggregates [21] . Probably, maintaining of NSPCs cultures in serum-containing media results in the accumulation of the least differentiated cells in neurospheres, while more differentiated cells adhere to cultural plastic and are eliminated at passaging.…”
Section: Discussionmentioning
confidence: 99%
“…The primary neural stem cells were obtained from the cerebral cortex of embryo at 18 days gestation rats as described previously [20]. In brief, the cerebral cortices were digested with 0.25% trypsin, and then the cell suspension was seeded into six-well plates pre-coated with poly- l -lysine.…”
Section: Methodsmentioning
confidence: 99%